PSYCHOPHYSIOLOGICAL AND PSYCHOLINGUISTIC FUNDAMENTALS OF TEACHING POLYSEMEUS WORDS TO PRIMARY SCHOOL STUDENTS (Scientific journal of the Fergana State University, 2023)
This article discusses the possibility of linguistic phenomena, the existence of polysemy in the language, the ability of people to call different things and events in one word, teaching primary school students to work with polysemantic vocabulary will improve the quality of students' vocabulary. The organization of stage-by-stage teaching of complex aspects of polysemy in the process of teaching the native language of primary school students in school is considered. The article also describes the ability not only to distinguish the meanings of words with the help of lexical polysemy, but also to instill the idea that students' speech should be enriched with new meanings of words; describes the views of many scientists on the formation of polysemy of words in the minds of primary school students.